Upper Limb Deep Vein Thrombosis: A Case Report of an Increasingly Common Condition. - Chen, Alexander W.Y.; Oraii Yazdani, Kaveh; Candilio, Luciano (Journal of Tehran University Heart Center, 2018)
Upper limb deep vein thrombosis (DVT) is a less common phenomenon than lower limb DVT. Repeated trauma secondary to sport- or job-related arm movements and positions has been recognized as the predisposing factor for upper limb DVT. We describe a 38-year-old male computer programmer admitted with swelling and pain in his left upper limb. Venous duplex ultrasound confirmed the presence of axillary vein thrombosis. Coagulation studies for secondary thrombosis were unremarkable. The patient was treated with full anticoagulation using low molecular weight heparin and warfarin. On subsequent follow-up at 3 months, the patient was symptom free and duplex sonography showed no evidence of thrombosis.